Thermoelectric and Hybrid Generators in Wearable Devices and Clothes - Leonov, V.; Van Hoof, C.; Vullers, R.J.M. (2009 Sixth International Workshop on Wearable and Implantable Body Sensor Networks, 2009)
This paper discusses the necessity and ways of replacing batteries in BSNs and other wearable devices with energy scavengers. The stresses are made on thermoelectric energy converters of human body heat into electrical power and on rules of their designing. The reasons for and possible ways of hybridizing wearable thermoelectric converters with photovoltaic cells are discussed, too. The examples of energy scavengers, both wearable and in clothing, for self-powered wireless sensors are described.